Epidemiology of child mortality and challenges in child death review in Japan: The Committee on Child Death Review: A Committee Report. Issue 1 (11th March 2022) - Numaguchi, Atsushi; Mizoguchi, Fumitake; Aoki, Yasuhiro; An, Byongmung; Ishikura, Ayako; Ichikawa, Kotaro; Ito, Yurie; Uchida, Yoshiko; Umemoto, Masakazu; Ogawa, Yuichi; Osamura, Toshio; Obonai, Masatoshi; et al.
Abstract: We performed a retrospective survey and verification of the medical records of death cases of children (and adolescents; aged <18 years) between 2014 and 2016 in pediatric specialty training facilities in Japan. Of the 2, 827 registered cases at 163 facilities, 2, 348 cases were included. The rate of identified deaths compared with the demographic survey, was 18.2%–21.0% by age group. The breakdown of deaths was determined as follows: 638 cases (27.2%) were due to external factors or unknown causes, 118 (5.0%) were suspected to involve child maltreatment, 932 (39.7%) were of moderate or high preventability or were indeterminable. Further detailed verification was required for 1, 333 cases (56.8%). Comparison of the three prefectures with high rates of identified deaths in Japan revealed no significant differences, such as in the distribution of diseases, suggesting that there was little selection bias. The autopsy rate of deaths of unknown cause was 43.4%, indicating a high ratio of forensic autopsies. However, sufficient clinical information was not collected; therefore, thorough evaluations were difficult to perform. Cases with a moderate or high possibility of involvement of child maltreatment accounted for 5%, similar to previous studies. However, more objective evaluation is necessary. Preventable death cases including potentially preventable deaths accounted for 25%, indicating that proposals need to be made for specific preventive measures. Individual primary verification followed by secondary verification by multiple organizations is effective. It is anticipated that a child death review (CDR) system with such a multi‐layered structure will be established; however, the following challenges were revealed: The subjects of CDR are all child deaths. Even if natural death cases are entrusted to medical organizations, and complicated cases to other special panels, the numbers are very high. Procedures need to be established to sufficiently verify these cases. Although demographic statistics are useful for identifying all deaths, care must be taken when interpreting such data. Detailed verification of the cause of death will affect the determination of subsequent preventability. Verification based only on clinical information is difficult, so a procedure that collates non‐medical information sources should be established. It is necessary to organize the procedures to evaluate the involvement of child maltreatment objectively and raise awareness among practitioners. To propose specific preventive measures, a mechanism to ensure multiprofessional diverse perspectives is crucial, in addition to fostering the foundation of individual practitioners. To implement the proposed measures, it is also necessary to discuss the responsibilities and authority of each organization. Once the CDR system is implemented, verification of the system should be repeated. Efforts to learn from child deaths and prevent deaths that are preventable as much as possible are essential duties of pediatricians. Pediatricians are expected to undertake the identified challenges and promote and lead the implementation of the CDR system. This is a word‐for‐word translation of the report in J. Jpn. Pediatr . Soc . 2019; 123 (11): 1736–1750, which is available only in the Japanese language.